Features of primary school students’ perceptions of themselves and their friends in friendly relations - Viktorovna Minaeva, Elena (2021)
The article is devoted to the study of some aspects of friendship relations in primary school age. It presents original diagnostic methods for studying friendship relations in elementary school students: “Qualities of a friend” and “What kind of friend am I?”. The object of the diagnostic techniques is the significant qualities of a friend, the features of the respondents’ attitude to the identified qualities, and the awareness of their contribution to friendly relations. The procedure of administering the techniques is described and the parameters of evaluation of the results, the features of their processing, and recommendations to experts on the use of the given diagnostic tools are allocated. The procedure of testing the validity and reliability of the diagnostic techniques is described. The deployed testing methods include expert evaluation and retesting. The results of the study of friendly relations in primary school students are described. The specific characteristics of the dynamic of friendly relations in primary school students are identified, The respondents demonstrate the ability to allocate a significant number of qualities important for friendship. By the end of the age period, children reorient from the external qualities of a friend to the internal ones characterizing the foundation of the relationships, empathy, support, and moral qualities. There is a development of reflection of relations, understanding of one’s own participation in friendship. The prospects for further study of the designated topic are defined.